Turbocharger rotor vibration reduction methodology with an active control scheme. (December 2021) - Mutra, Rajasekhara Reddy; Srinivas, J; Shaik, Jakeer Hussain; Chinna Obaiah, Maddela; Balamurali, Gunji; Kumar, Puneet
The turbocharger rotors are often supported on the dual film floating ring bearings that are meant for high-speed applications. The damping ability of these bearings is relatively high. However, due to highly nonlinear bearing forces, often system instability occurs. The present work focuses on the dynamic analysis and active vibration control studies of a practical turbocharger rotor system with the use electromagnetic actuator (EMA) system. Initially, the system is analyzed using the finite element approach. The inner and outer film forces are considered along with rotor imbalance forces. The dynamic responses at the critical operating speeds are obtained numerically. To minimize the vibration amplitudes, a tiny EMA system is installed at one of the nodes along the shaft. The effect of the EMA parameters such as the number of turns of winding coil around a pole ( N c ) and pole-face area ( A a ) on the response of the system is studied. Further, an open-loop control configuration is practically studied by using a vibration shaker at the bearing node under different operating speeds, and the percentage reduction in critical vibration amplitudes is recorded. The EMA system is effectively controlling the high-speed rotor system vibrations. The EMA parameters N c and A a are influencing the system vibration response. Further, an experimental result has given considerable vibration reduction with the present approach.